A High Starch Diet Alters the Composition of the Intestinal Microbiota of Largemouth Bass Micropterus salmoides, Which May Be Associated With the Development of Enteritis - Huang, Xiaoli; Zhong, Liang; Kang, Qin; Liu, Sha; Feng, Yang; Geng, Yi; Chen, Defang; Ou, Yangping; Yang, Shiyong; Yin, Lizi; Luo, Wei (Frontiers in Microbiology, 2021)
Starch is an inexpensive feed ingredient that has been widely used in fish feed. However, starch utilization by carnivorous fish is limited and excess starch is detrimental to the health of the organism. High starch diets often lead to liver damage, but the effects on the intestine are often overlooked. Therefore, in this study, two isonitrogenous and isolipidic semi-pure diets (NC: 0% α-starch, HC: 22% α-starch) were formulated and fed to largemouth bass (Micropterus salmoides) for 45d. The effects of the high starch diet on the intestine of largemouth bass were comprehensively investigated by intestinal microbiota, histopathology, ultrastructural pathology, and enzymology analyses. Feeding the HC diet did not affect the growth of largemouth bass during the experimental period. However, the high starch diet led to a reduction in the diversity and abundance of intestinal microbiota in largemouth bass, with a significant increase in the abundance of harmful bacteria (Aeromonas) and a decrease in the abundance of beneficial bacteria (Clostridium, Lactobacillus and Bifidobacterium). Feeding the HC diet caused the development of enteritis, with goblet cell hyperplasia, epithelial necrosis and detachment and inflammatory cell infiltration, and leading to enlarged apical openings and mitochondrial damage in goblet cells. Long-term feeding of the HC diet inhibited intestinal α-amylase activity. changes in the intestinal microbiota, such as an increase in Aeromonas and a decrease in Clostridium, Lactobacillus, and Bifidobacterium, may be closely related to the development of enteritis. Therefore, adding these beneficial bacteria as probiotics may be an effective way to prevent damage to the intestine of largemouth bass from a high carbohydrate diet. Our results suggest reducing the amount of starch added to the largemouth bass diets. This study provides a reference for protecting the largemouth bass gut during modern intensive culture.